Thoracoscopic wedge resection in single-lung patients - Zampieri, Davide (J Thorac Dis, 2018)
BACKGROUND: The thoracoscopic approach has become a standard procedure in the field of lung resections. However, its advantage in single-lung patients has not yet been well studied. We describe a series of successful thoracoscopic wedge resections in patients presenting with lung cancer after contralateral pneumonectomy. METHODS: Eight patients, with a previous pneumonectomy (5 right and 3 left) for lung cancer, underwent resection for a suspicious neoplasm on the remaining lung. All lesions were detected in the asymptomatic phase during regular follow-up after pneumonectomy based on repeated computer tomography (CT). Only single peripheral lesions less than 2 cm were eligible for wedge resection were eligible for surgery. Video-assisted thoracoscopic, margin-free tumor wedge resections, were performed during apnea windows with the lung in a deflated position. RESULTS: All patients were treated by a wedge resections smaller than a single segment. Only one patient needed a mini-thoracotomy conversion to accomplish a safe margin-free resection. Median total surgical operative time was 37 minutes. There were no postoperative deaths, while morbidity was 12.5%. CONCLUSIONS: Thoracoscopic surgery represents a feasible surgical option in selected patients after contralateral pneumonectomy, with careful preoperative assessment and using short apnea windows in good collaboration with anesthesiologists. Histological definition, made possible by the surgical-procedure, gives patients the possibility to eventually undergo further targeted therapies. Randomized prospective trials are necessary to assess the best management of peripheral small lung nodules in single-lung patients, in particular to define which patients can benefit from a surgical approach.